Benefits of multistrain bacteria formulations for health. (August 2018) - Laterza, L.; Gibiino, G.; Scaldaferri, F.; Gasbarrini, A.
Graphical abstract: Highlights: Not all multistrain probiotics have been adequately evaluated in clinical trials. Double-blind, placebo-controlled RCTs provided the best evidences. L. acidophilus is the most represented species in multistrain products. The choice of the right probiotic should be based on available evidences. Abstract: Gut microbiota dysfunction is associated with multiple gastrointestinal and extra-gastrointestinal diseases, thus the possibility of its modulation with prebiotics, probiotics and symbiotics has gained interest in the last years. Many probiotics are available on the market and products characterized by combination of multiple strains have been proposed as particularly effective. However, evidences supporting their efficacy are often inadequate and not homogenous. We reviewed available data on clinical efficacy of multistrain probiotics and symbiotics in gastrointestinal diseases in adults, focusing on data from randomised, double-blind, placebo-controlled clinical trials. Twenty-nine multistrain products satisfied inclusion criteria. The principal areas of application are irritable bowel syndrome, Helicobacter pylori eradication and antibiotic-associated diarrhoea. The most represented probiotic species in the different probiotic formulations was L. acidophilus . The combination of L. paracasei, L. plantarum, L. acidophilus, L. delbrueckii subsp. bulgaricus, B. longum, B. infantis, B. breve and S. thermophilus (VSL#3) showed the highest number of RCTs.